Understanding and Overcoming the Challenges Posed by Electrode/Electrolyte Interfaces in Rechargeable Magnesium Batteries - Mizuno, Fuminori; Singh, Nikhilendra; Arthur, Timothy S.; Fanson, Paul T.; Ramanathan, Mayandi; Benmayza, Aadil; Prakash, Jai; Liu, Yi-Sheng; Glans, Per-Anders; Guo, Jinghua (Frontiers in Energy Research, 2014)
Magnesium (Mg) battery technologies have attracted attention as a high energy-density storage system due to the following advantages: (1) potentially high energy-density derived from a divalent nature, (2) low-cost due to the use of an earth-abundant metal, and (3) intrinsic safety aspect attributed to non-dendritic growth of Mg. However, these notable advantages are downplayed by undesirable battery reactions and related phenomena. As a result, there are only a few working rechargeable Mg battery systems. One of the root causes for undesirable behavior is the sluggish diffusion of Mg2+ inside a host lattice. Another root cause is the interfacial reaction at the electrode/electrolyte boundary. For the cathode/electrolyte interface, Mg2+ in the electrolyte needs a solvation–desolvation process prior to diffusion inside the cathode. Apart from the solid electrolyte interface (SEI) formed on the cathode, the divalent nature of Mg should cause kinetically slower solvation–desolvation processes than that of Li-ion systems. This would result in a high charge-transfer resistance and a larger overpotential. On the contrary, for the anode/electrolyte interface, the Mg deposition and dissolution process depends on the electrolyte nature and its compatibility with Mg metal. Also, the Mg metal/electrolyte interface tends to change over time, and with operating conditions, suggesting the presence of interfacial phenomena on the Mg metal. Hence, the solvation–desolvation process of Mg has to be considered with a possible SEI. Here, we focus on the anode/electrolyte interface in a Mg battery, and discuss the next steps to improve the battery performance.